4,83
Пошаговое объяснение:
5,6+(-11/8)-х=-0,605
5,6-1,375-х=-0,605
5,6-1,375+0,605=х
х=4,83
( (5,6 + (-1. 1/8) ) - х = -0,605
(5,6 - 1. 1/8) - х = -0,605
(5,6 - 1,125) - х = -0,605
4,475 - х = -0,605
х = 4,475 - (-0,605)
х = 4,475 + 0,605
х = 5,08
4,83
Пошаговое объяснение:
5,6+(-11/8)-х=-0,605
5,6-1,375-х=-0,605
5,6-1,375+0,605=х
х=4,83
Пошаговое объяснение:
( (5,6 + (-1. 1/8) ) - х = -0,605
(5,6 - 1. 1/8) - х = -0,605
(5,6 - 1,125) - х = -0,605
4,475 - х = -0,605
х = 4,475 - (-0,605)
х = 4,475 + 0,605
х = 5,08